Rencana Tata Ruang Wilayah dalam Perspektif Perencanaan Pembangunan Wilayah (Studi pada Badan Perencanaan Pembangunan Daerah Kota Probolinggo) - Widodo, Setio (Jurnal Ilmiah Administrasi Publik, 2017)
This paper examines the relevance of spatial plan with the regional development plans and their impact on development, particularly in the city of Probolinggo. Integration of spatial plans are realized in RTRW with development plans are realized in RPJPD and RPJMD becomes very important, because the existing strategy in the RTRW or RPJPD do will be impossible if it is not accommodated in RPJMD. The results showed linkage substantive less robust among RTRW with RPJMD Kota Probolinggo, so not all guidelines for development in the RTRW can be done, and as a conclusion RTRW considered not able to provide a positive influence for sustainable development in the city of Probolinggo, especially in terms of environmental quality and equity development.